Calving controlled by melt-under-cutting: detailed calving styles revealed through time-lapse observations. Issue 78 (30th January 2019) - How, Penelope; Schild, Kristin M.; Benn, Douglas I.; Noormets, Riko; Kirchner, Nina; Luckman, Adrian; Vallot, Dorothée; Hulton, Nicholas R. J.; Borstad, Chris
Abstract: We present a highly detailed study of calving dynamics at Tunabreen, a tidewater glacier in Svalbard. A time-lapse camera was trained on the terminus and programmed to capture images every 3 seconds over a 28-hour period in August 2015, producing a highly detailed record of 34 117 images from which 358 individual calving events were distinguished. Calving activity is characterised by frequent events (12.8 events h −1 ) that are small relative to the spectrum of calving events observed, demonstrating the prevalence of small-scale calving mechanisms. Five calving styles were observed, with a high proportion of calving events (82%) originating at, or above, the waterline. The tidal cycle plays a key role in the timing of calving events, with 68% occurring on the falling limb of the tide. Calving activity is concentrated where meltwater plumes surface at the glacier front, and a ~ 5 m undercut at the base of the glacier suggests that meltwater plumes encourage melt-under-cutting. We conclude that frontal ablation at Tunabreen may be paced by submarine melt rates, as suggested from similar observations at glaciers in Svalbard and Alaska. Using submarine melt rate to calculate frontal ablation would greatly simplify estimations of tidewater glacier losses in prognostic models.